Frequency shift keying modem system / Hanim Amin and Fadhilah Kassim - Amin, Hanim; Kassim, Fadhilah (1993)
The connection between a data communication device and the Public Switching Telephone Network (PSTN) requires a device called modem. A modem is an acronym for modulator-demodulator. It converts digital data signals to suitable audio signals at the transmitter, and the process referred to as modulation; while it converts the audio signals back 2into digital data signals at the receiver end, commonly referred to as demodulation. Therefore modem was used to send and receive digital data.